2021
DOI: 10.1101/2021.11.22.469359
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Visual Attention in The Fovea and The Periphery during Visual Search

Abstract: SummaryVisual search depends on both the foveal and peripheral visual system, yet the foveal attention mechanisms is still lack of insights. We simultaneously recorded the foveal and peripheral activities in V4, IT and LPFC, while monkeys performed a category-based visual search task. Feature attention enhanced responses of Face-selective, House-selective, and Non-selective foveal cells in visual cortex. While foveal attention effects appeared no matter the peripheral attention effects, paying attention to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 50 publications
(97 reference statements)
0
1
0
Order By: Relevance
“…5B ; P > 0.05). This result suggested that the processing in the fovea influenced the processing in the periphery, consistent with our prior report [16].…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…5B ; P > 0.05). This result suggested that the processing in the fovea influenced the processing in the periphery, consistent with our prior report [16].…”
Section: Resultssupporting
confidence: 93%
“…In the present study, we further revealed systematic differences in response profile and functional connectivity between foveal units and peripheral units. Moreover, our prior study revealed a bidirectionally interactive loop between parallel feature attention and serial saccade selection [16]. Our present study further corroborated these findings by showing the interaction and coordination between foveal and peripheral processing for spatial attention and saccade selection.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Although we only tested DAE-NR with mice neural data, the pipeline of DAE-NR can be easily extent to the neurons of primates (e.g. monkey [43] or human). Beyond DAE-NRs, there are many future directions that combine artificial intelligence and brain intelligence that are worthy of investigation.…”
Section: Discussionmentioning
confidence: 99%